(untitled) (Journal of Oriental Studies, 2016)
This article is devoted to the study of slang as a separate layer reduced vocabulary, as well as the diffi culties faced by the translator when working on an adequate transfer of elements of slang from the original language into the target language. The purpose of the master’s work is the study of the basic techniques of translation in the transmission of slang items from English to Russian and quantitative determination of the frequency of the use of a transfer admission.